Oxygen Vacancies Confined in Ultrathin Indium Oxide Porous Sheets for Promoted Visible-Light Water Splitting - Lei, Fengcai; Sun, Yongfu; Liu, Katong; Gao, Shan; Liang, Liang; Pan, Bicai; Xie, Yi (Journal of the American Chemical Society, 2014)
Finding an ideal model for disclosing the role of oxygen vacancies in photocatalysis remains a huge challenge. Herein, O-vacancies confined in atomically thin sheets is proposed as an excellent platform to study the O-vacancy–photocatalysis relationship. As an example, O-vacancy-rich/-poor 5-atom-thick In2O3 porous sheets are first synthesized via a mesoscopic-assembly fast-heating strategy, taking advantage of an artificial hexagonal mesostructured In-oleate complex. Theoretical/experimental results reveal that the O-vacancies endow 5-atom-thick In2O3 sheets with a new donor level and increased states of density, hence narrowing the band gap from the UV to visible regime and improving the carrier separation efficiency. As expected, the O-vacancy-rich ultrathin In2O3 porous sheets-based photoelectrode exhibits a visible-light photocurrent of 1.73 mA/cm2, over 2.5 and 15 times larger than that of the O-vacancy-poor ultrathin In2O3 porous sheets- and bulk In2O3-based photoelectrodes.